Collaborative Governance in Countermeasures Edit in Bangka Regency, Bangka Belitung Islands Province - Suyanti, Then; Maryani, Dedeh; Polyando, Petrus; Achmad, Mansyur (Journal Of Social Science (JoSS), 2025)
This study examines the application of collaborative governance in stunting prevention in Bangka Regency, Bangka Belitung Islands Province. Through a qualitative approach and descriptive research design, this study identifies challenges, driving factors, and inhibitions in the implementation of collaboration between sectors involving local governments, the private sector, communities, and academia. The results show that despite the shared commitment, coordination between sectors is limited, limited resources, and differences in perceptions among stakeholders are the main challenges. This study provides recommendations to strengthen facilitative leadership and more inclusive institutional design to increase the effectiveness of collaboration in stunting prevention